Mesoporous Mg-doped hydroxyapatite nanorods prepared from bio-waste blue mussel shells for implant applications. Issue 18 (15th December 2020) - Karunakaran, Gopalu; Cho, Eun-Bum; Kumar, Govindan Suresh; Kolesnikov, Evgeny; Janarthanan, Gopinathan; Pillai, Mamatha Muraleedharan; Rajendran, Selvakumar; Boobalan, Selvakumar; Sudha, Kattakgoundar Govindaraj; Rajeshkumar, Mohan Prasanna
Abstract: The most important problem in post orthopedic surgery is implant infections developed by infectious micro-organisms. An alternative strategy needs to resolve this problem through creating a biomaterial with the addition of potential antibacterial activity. The foremost objective of this study is to develop magnesium (Mg)-doped mesoporous hydroxyapatite (HAp) nanorods using polyvinylpyrrolidone-assisted microwave synthesis by utilizing seashell bio-wastes to inhibit implant infections. The XRD, Raman spectroscopy, and FT-IR results expose that the produced HAp nanoparticles possesses hexagonal crystal structure. The morphological topographies corroborate that the acquired pure HAp consists of mesoporous nanorods with size of 10–15 nm (width) and 50–90 nm (length). Further, Mg-doped HAp nanoparticles, namely, MgHAp-1, MgHAp-2, and MgHAp-3 were also found alike mesoporous nanorods; however, with variations in sizes of 5–10, 10–15, 15–20 nm width and 50–65, 50–70, 50–80 nm length, respectively. Specific surface area was 47.2, 49.3, 113.0, and 25.7 m 2  g −1, and with pore diameters of 3.79, 3.96, 6.07, and 7.77 nm, respectively, for the produced pure HA, MgHAp-1, MgHAp-2, and MgHAp-3 particles. The cytotoxicity and antibacterial analyses confirm that Mg-doped HAp nanorods are non-toxic with effective antibacterial properties. Therefore, it is clear that polyvinylpyrrolidone-assisted microwave synthesis method is an excellent way for the rapid manufacturing of HAp nanoparticles with diverse ranges and mesoporous morphology for its application as implant materials.